'Beautiful one day, perfect the next...' Becoming Queensland 1859-1909 - Haebich, Anna (Townsville City Council, 2013)
Since colonial times, Queensland has been touted as a place that fired the imagination. People of various motivations were drawn here by fanciful visions of the frontier, where vast grasslands and exotic species beckoned settlers to partake in classification and conquest, where South Sea Islanders were deployed into plantation work that was deemed unsuitable for Europeans, and where newcomers were inspired to become farmers. ... This series was delivered as public lectures from late 2009 to 2012 ... The essays cover themes of environmental history, race conflict history, and cultural history.